Time-varying K factor of the mm-Wave Vehicular Channel: Velocity, Vibrations and the Road Quality Influence - Blumenstein, Jiří; Prokeš, Aleš; Vychodil, Josef; Pospíšil, Martin; Mikulášek, Tomáš (IEEE, 2017)
Abstract—This paper evaluates real-world intra-vehicle millimeter-wave (mmWave) channel measurements performed in a vehicular environment. Utilizing a correlative time-domain channel sounder, we demonstrate the dependency of the timevarying Rician K factor on the road quality and instantaneous velocity of the measured vehicle. Vibrations caused by the movement of the vehicle together with mechanical properties of the vehicle’s chassis leads to a mutual movement of the transmitting (TX) and the receiving (RX) antennas mounted on the front windshield and on the rear quarter window respectively. The channel sounding is performed in a frequency bandwidth from 59.1 GHz to 64GHz with 50 GS/s sampling frequency.

Abstract—This paper evaluates real-world intra-vehicle millimeter-wave (mmWave) channel measurements performed in a vehicular environment. Utilizing a correlative time-domain channel sounder, we demonstrate the dependency of the timevarying Rician K factor on the road quality and instantaneous velocity of the measured vehicle. Vibrations caused by the movement of the vehicle together with mechanical properties of the vehicle’s chassis leads to a mutual movement of the transmitting (TX) and the receiving (RX) antennas mounted on the front windshield and on the rear quarter window respectively. The channel sounding is performed in a frequency bandwidth from 59.1 GHz to 64GHz with 50 GS/s sampling frequency.
Time-varying K factor of the mm-Wave Vehicular Channel: Velocity, Vibrations and the Road Quality Influence
Keywords: millimeter-wave; mmWave; channel measurements; Rician K factor; millimeter-wave; mmWave; channel measurements; Rician K factor